2021
DOI: 10.3390/wevj12030149
|View full text |Cite
|
Sign up to set email alerts
|

Back EMF Waveform Comparison and Analysis of Two Kinds of Electrical Machines

Abstract: In this study, the back electromotive force (EMF) waveforms of a flux switching permanent magnet (FSPM) machine and variable flux memory permanent magnet (VFMPM) machine with same main dimension were researched. Firstly, the simulation result showed that the maximum amplitude of phase back EMF waveform of FSPM machine was 245% larger than that of the VFMPM machine, and this was verified by the experimental result (243%). Secondly, the phase back EMF harmonics of the FSPM machine and VFMPM machine were compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The 2D finite element analysis (FEA) was performed to validate the brushless operation of the proposed machine system. In [11], the back electromotive force (EMF) waveforms of a flux-switching permanent magnet (FSPM) machine and a variable flux memory permanent magnet (VFMPM) machine with the same main dimension were researched. The simulation results showed that the maximum amplitude of the phase back EMF waveform of the FSPM machine was 245% larger than that of the VFMPM machine, and this was verified by the experimental results (243%).…”
Section: Overview Of Contributionmentioning
confidence: 99%
“…The 2D finite element analysis (FEA) was performed to validate the brushless operation of the proposed machine system. In [11], the back electromotive force (EMF) waveforms of a flux-switching permanent magnet (FSPM) machine and a variable flux memory permanent magnet (VFMPM) machine with the same main dimension were researched. The simulation results showed that the maximum amplitude of the phase back EMF waveform of the FSPM machine was 245% larger than that of the VFMPM machine, and this was verified by the experimental results (243%).…”
Section: Overview Of Contributionmentioning
confidence: 99%
“…To improve the torque performance of the doubly salient electromagnetic machine, paper [9] proposes an optimization method of the magnetomotive force based on the optimized rotor pole geometry. Paper [10] deals with the comparison of the back electromotive force for two different electrical machines with the same dimensions. This analysis provides some qualitative advice for the application, optimization, and control methods.…”
Section: Optimal Induced Voltage and Force Generationmentioning
confidence: 99%
“…Moreover, batteries can be utilized with various methods to ensure their maximum usage (Cui, 2021). However, this requires significant effort due to the complexity of the circuitry involved.…”
Section: Introductionmentioning
confidence: 99%